PENGARUH KINERJA KEUANGAN, KESEMPATAN INVESTASI, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Moehamad Rizki Bagoes Setiawan; Darsono Darsono (Diponegoro Journal of Accounting, 2023)
Increasing company value is not only a measure of success, but also a determining factor for a company's survival in an increasingly competitive market. Therefore, it is important for companies to understand the factors that influence the increase in company value, especially in the context of disclosing complex and varied company information. A more in-depth study on the influence and characteristics of company information disclosure can provide valuable insights for companies in making strategic decisions to increase company value and maintain their competitive advantage. This research aims to examine the effect of financial performance consisting of liquidity, profitability, solvency, investment opportunity, and corporate social responsibility on company value.Data was collected through the documentation method from manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2021 timeframe using a purposive sampling technique. The sample consists of 380 companies selected from a total of 717 existing companies. The analytical method used is multiple linear regression.      The results showed that liquidity, solvency, investment opportunities, and corporate social responsibility have a significant positive effect on firm value, while earnings do not have a significant positive effect on firm value.